1996
DOI: 10.1055/s-2007-972883
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Short-Term Aerobic Training on Blood Lipids in Healthy 10-12 Year Old Children

Abstract: This study was designed to examine the ability an endurance exercise training program to alter blood levels of cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides in children. Thirty-one sixth grade students age 10-12 years (20 girls, 11 boys) who were healthy and active volunteered for participation. The training program consisted of 13 weeks of aerobic activities three days a week, 25 minutes per session, with training intensity assessed by heart rate monitors. Serum lipids and maximal oxygen up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 1 publication
3
40
2
Order By: Relevance
“…Because of the inherent challenges of research that involves objective PA measures, the review team decided not to downgrade for risk of bias if the only potential sources of bias identified were use of a convenience sample or lack of exposure/outcome blinding. samples), ranging from 31 (Rowland et al 1996) to 7495 (Tudor-Locke et al 2011) participants. Included studies were conducted in 31 different countries, and mean baseline age ranged from 5.1 to 17.7 years.…”
Section: Risk Of Bias and Evidence Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the inherent challenges of research that involves objective PA measures, the review team decided not to downgrade for risk of bias if the only potential sources of bias identified were use of a convenience sample or lack of exposure/outcome blinding. samples), ranging from 31 (Rowland et al 1996) to 7495 (Tudor-Locke et al 2011) participants. Included studies were conducted in 31 different countries, and mean baseline age ranged from 5.1 to 17.7 years.…”
Section: Risk Of Bias and Evidence Quality Assessmentmentioning
confidence: 99%
“…5/6 studies reported null effects of PA intervention on adiposity outcomes (Rowland et al 1996;Pangrazi et al 2003;Williams and Warrington 2011;Huang et al 2012;Duncan et al 2012) VERY LOW j 1/6 studies reported lower odds of overweight/obesity half way through (1 y) a school/afterschool-based total PA intervention program, at post-test (2 y) and at 2-y follow-up (Sigmundova and Sigmund 2012) 11 629 (14) Longitudinal k Risk of bias l No serious inconsistency…”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these ®ndings, some studies have found no changes in lipid and lipoprotein concentrations following ET in children. 7,8 The reason for these discrepancies is unknown, but may be related to whether the subjects participated in an adequate amount of ET and whether the subjects were obese at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…20 A descriptive study of ®fth grade children showed that usual activity level had no effect on lipids. 21 In an extensive review of studies of physical activity and lipids in adolescents and adults, Armstrong and Simons-Morten 22 concluded that the effects of physical activity on adolescent and adult blood lipids are equivalent.…”
Section: Introductionmentioning
confidence: 99%